2020
DOI: 10.3390/antib9030033
|View full text |Cite
|
Sign up to set email alerts
|

From Anti-SARS-CoV-2 Immune Responses to COVID-19 via Molecular Mimicry

Abstract: Aim: To define the autoimmune potential of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Methods: Experimentally validated epitopes cataloged at the Immune Epitope DataBase (IEDB) and present in SARS-CoV-2 were analyzed for peptide sharing with the human proteome. Results: Immunoreactive epitopes present in SARS-CoV-2 were mostly composed of peptide sequences present in human proteins that—when altered, mutated, deficient or, however, improperly functioning—may associate with a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 88 publications
(186 reference statements)
5
103
0
1
Order By: Relevance
“…Accordingly, lungs and airways dysfunctions associated with SARS-CoV-2 infection might be explained by the sharing of peptides between SARS-CoV-2 spike glycoprotein and alveolar lung surfactant proteins [ 2 ]. In support of this thesis, additional reports [ 5 8 ] highlight molecular mimicry and cross-reactivity as capable of explaining the SARS-CoV diseases. Of special interest, cross-reactive T cell recognition between circulating “common cold” coronaviruses and SARS-CoV-2 has been also suggested [ 9 ].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Accordingly, lungs and airways dysfunctions associated with SARS-CoV-2 infection might be explained by the sharing of peptides between SARS-CoV-2 spike glycoprotein and alveolar lung surfactant proteins [ 2 ]. In support of this thesis, additional reports [ 5 8 ] highlight molecular mimicry and cross-reactivity as capable of explaining the SARS-CoV diseases. Of special interest, cross-reactive T cell recognition between circulating “common cold” coronaviruses and SARS-CoV-2 has been also suggested [ 9 ].…”
Section: Introductionsupporting
confidence: 60%
“…Instead, no or a lowest number of common peptides are present in mammals that have no major pathologic sequelae once infected by SARS-CoV-2 [ 10 12 ]. Hence, the data appear to be an indisputable proof in favor of molecular mimicry as a potential mechanism that can contribute to or cause the SARS-CoV-2 associated diseases [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above analyzed COVID-19 vaccine safety considerations become even more cogent in light of the fact that cross-reactivity might represent the mechanism underlying the immunopathology and the disease multitude associated with the coronavirus infection [ 145 ]. The rationale is that the sharing of peptides between SARS-CoV-2 and human proteins might trigger immune responses hitting not only the virus but also the human proteins, with consequent autoimmune pathologies in the human host [ 146 ].…”
Section: Resultsmentioning
confidence: 99%
“…More than 1/3 of peptides that are immunogenic were found to be homologous to the proteins that are significant in the adaptive immune system. Kanduc [50] suggested that there is an extensive range of health disorders, related to probable autoimmunity reactions against peptides of the human proteome, which have homology with the immunogenic peptides of SARS-CoV-2. Also, it was indicated in another study [51] that cerebrospinal fluids from the patients of COVID-19 were suggestive of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%